Perbandingan Fitur Smartphone, Pemanfaatan Dan Tingkat Usability Pada Android Dan iOS Platforms - Sasa Ani Arnomo; Hendra Hendra (Universitas Islam Sumatera Utara, 2019)
Android dan iOS nowadays have become the most dominating operating system in smartphone markets. These two operating system continue to grow rapidly in terms of technology as well as the number of devices that exist in the world. However, consumers are still lacking of understanding on how to compare these two operating systems from various of aspects. So, this research is being conducted with the purpose to learn about the comparison of these two operating system in terms of features, utilizations and usability. Method that is being used in this research is descriptive analysis which in comparison of features and utilizations are using documentation and observation as data collection technique. For usability comparison is using questionnaire technique. Result of the research has shown that Android and iOS each have their unique features such as Google Hangouts with i-Message and Smart Caller ID with Facetime. Afterwards, comparison of utilizations has shown that Android is mostly being used for communication as for iOS more for information searching. Meanwhile, for descriptive result of usability has shown that Android and iOS have the same level of ease of use which is good.